Pengaruh Sales Growth, Cash Holdings dan Audit Quality terhadap Manajemen Laba - Saptomo, Shafia Carina; Mulyani, Erly (Jurnal Nuansa Karya Akuntansi, 2025)
This study aims to examine the effect of sales growth, cash holdings, and audit quality on earnings management. The type of research is causal associative with a quantitative approach. The data used is obtained from the annual reports of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sample selection method uses purposive sampling, resulting in 277 samples from 75 companies. This study uses multiple linear regression analysis to test the hypothesis, assisted by the SPSS version 26 program. The results show that cash holdings and audit quality do not have a significant effect on earnings management, while sales growth has a positive and significant effect on earnings management. For further research, it is recommended to select other variables that affect earnings management.